High frequency of tumours in Mulibrey nanism - Karlberg, Niklas; Karlberg, Susann; Karikoski, Riitta; Mikkola, Sakari; Lipsanen-Nyman, Marita; Jalanko, Hannu (The Journal of pathology, 2009)
Mulibrey nanism (MUL) is a monogenic disorder with prenatal-onset growth failure, typical clinical characteristics, cardiopathy and tendency for a metabolic syndrome. It is caused by recessive mutations in the TRIM37 gene encoding for the peroxisomal TRIM37 protein with ubiquitin-ligase activity. In this work, the frequency and pathology of malignant and benign tumours were analysed in a national cohort of 89 Finnish MUL patients aged 0.7-76 years. The subjects had a clinical and radiological evaluation, and histological and immunohistocemical analyses on specimens obtained from biopsy, surgery or autopsy, were performed. The results show that the MUL patients have disturbed architecture with ectopic tissues and a high frequency of both benign and malignant tumours detectable in several internal organs. A total of 210 tumorous lesions were detected in 66/89 patients (74%). Fifteen malignancies occurred in 13 patients (15%), seven of them in the kidney (five Wilms' tumours), three in the thyroid gland, two gynaecological cancers, one gastrointestinal carcinoid tumour, one neuropituitary Langerhans cell histiocytosis and one case of acute lymphoblastic leukaemia (ALL). Tumours detected by radiology in the liver and other organs mainly comprised strongly dilated blood vessels (peliosis), vascularized cysts and nodular lesions. The lesions showed strong expression of the endothelial cell markers CD34 and CD31 as well as the myocyte marker α-smooth muscle actin (α-SMA). Our findings show that MUL is associated with frequent malignant tumours and benign adenomatous and vascular lesions, as well as disturbed organ development. Copyright © 2009 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.